Core‐shell fibrous scaffold as a vehicle for sustained release of retinal pigmented epithelium‐derived factor (PEDF) for photoreceptor differentiation of conjunctiva mesenchymal stem cells. Issue 12 (23rd October 2017) - Nasehi, Fatemeh; Karshenas, Mohsen; Nadri, Samad; Barati, Ghasem; Salim, Ahdiye
Abstract: Coaxial electrospinning technique was introduced as a flexible and promising technique for the fabrication of core‐shell fibrous scaffold from poly ethylene glycol/poly caprolactone (PEG/PCL), where retinal pigmented epithelium‐derived factor (PEDF) was encapsulated in the core, for photoreceptor differentiation of conjunctiva mesenchymal stem cells (CJMSCs) seed on scaffolds. The morphology and structure of fibers were characterized using SEM and TEM and photoreceptor differentiation was examined by quantitative real time PCR (qPCR). Release study showed that, a sustained release of PEDF from PEG/PCL scaffold was observed over 14 days. qPCR analysis demonstrated that rhodopsin (as a main photoreceptor gene) was significantly expressed in CJMSCs cultured on scaffold loaded with PEDF. According to the result, the core‐shell scaffold loaded with PEDF (PEG + PEDF)/PCL) has superior control over factor release profile and has a potential for guiding photoreceptor differentiation of mesenchymal stem cells and promoting retinal regeneration. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 3514–3519, 2017.